Spatial econometric model of the spillover effects of financial development on carbon emissions: A global analysis - Isma Samreen; Muhammad Tariq Majeed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
This study investigates the impact of financial development (FD) on CO2 emissions in the presence of economic growth, industrial growth, and renewable energy consumption. The sample size consists of panel of 89 countries for the period 1992-2014. The empirical analysis has been done by applying spatial econometrics techniques for exploring the spillover effects from the neighboring countries. The results demonstrate that spatial dependency exists among the sample economies. The spatial segregation analysis reveals that both local (direct) and spillover (indirect) financial development effects significantly lower local carbon emissions. Furthermore, the results demonstrate that in developed countries FD lowers the CO2 emissions whereas in developing countries FD increases the carbon emissions. The findings are useful for economic policy makers for devising economic and environment related policies by considering the intensity of FD spatial effects in the local economy's pollution level. The findings of this study are also useful for highlighting the fact that whether local economy's environment improved (or deteriorated) because of its own initiatives (pressure) for (on) environment or due to other country's initiatives (pressure) regarding FD.
Keywords: 330; financial development; economic growth; industrial growth; renewable energy consumption; spillover effect; CO2 emissions; spatial analysis